Recent Advances in the Catalytic Hydroconversion of 5-Hydroxymethylfurfural to Valuable Diols - Huang, Zexing; Wang, Jianhua; Lei, Jing; Zhao, Wenguang; Chen, Hao; Yang, Yongjun; Xu, Qiong; Liu, Xianxiang (Frontiers in Chemistry, 2022)
Biomass, a globally available resource, is a promising alternative feedstock for fossil fuels, especially considering the current energy crisis and pollution. Biomass-derived diols, such as 2,5-bis(hydroxymethyl)furan, 2,5-bis(hydroxymethyl)-tetrahydrofuran, and 1,6-hexanediol, are a significant class of monomers in the polyester industry. Therefore, the catalytic conversion of biomass to valuable diols has received extensive research attention in the field of biomass conversion and is a crucial factor in determining the development of the polyester industry. 5-Hydroxymethylfurfural (HMF) is an important biomass-derived compound with a C6-furanic framework. The hydroconversion of HMF into diols has the advantages of being simple to operate, inexpensive, environmentally friendly, safe, and reliable. Therefore, in the field of diol synthesis, this method is regarded as a promising approach with significant industrialization potential. This review summarizes recent advances in diol formation, discusses the roles of catalysts in the hydroconversion process, highlights the reaction mechanisms associated with the specificities of each active center, and provides an outlook on the challenges and opportunities associated with the research on biomass-derived diol synthesis.